Bortezomib: a new therapeutic option for POEMS syndrome - KOCAKAYA, OZAN (WILEY-BLACKWELL PUBLISHING, INC, 2010)
Objective: POEMS syndrome with its classical five findings (Polyneuropathy, Organomegaly, Endocrinopathy, M protein, and Skin changes) is a rare multisystem disease. Proinflammatory and proangiogenic cytokines play important roles in its pathogenesis. Treatment options are still debated. Methods: We present a 65-year-old man with POEMS syndrome who was successfully treated with bortezomib. Results: After seven cycles of this protocol, serum M protein level declined to normal range, and near-to-complete remission was achieved. His symptoms of polyneuropathy improved dramatically. Conclusion: Bortezomib may be an effective and safe therapeutic option for patients with POEMS syndrome.
Keywords: Bortezomib; POEMS syndrome; polyneuropathy; STEM-CELL TRANSPLANTATION; BEVACIZUMAB THERAPY; PERIPHERAL-BLOOD; PATIENT